First Reports of Cladosporium tenuissimum Causing Leaf spots on Hydrangea macrophylla in Anhui province in China - Gu, Xin (Plant disease, 2024)
Forever Summer Hydrangea (Hydrangea macrophylla) is a common flowering plant in the Yangtze River Valley area of China, and it is widely cultivated globally (Chen et al. 2015). In July 2023, H. macrophylla leaves exhibiting visible diseased lesions were reported in a nursery in Wuhu, Anhui Province, China. The incidence reached 40% in a 0.2 ha area. The primary disease symptom was multiple irregular necrotic spots (0.5 to 1 mm in diameter) appearing on the leaves. These spots on the leaves were faded yellow around the perimeter and grayish brown in the center.). 15 leaf samples were sterilized with 75% alcohol and rinsed three times in sterile distilled water, then transferred to antibiotic-added potato dextrose agar (PDA) for incubation at 27°C. The colonies were fluffy, flocculent, or hairy, dark green, gray-green to gray-brown in color, and spreading or protruding punctate with a colorless halo on PDA. The conidiophores were brown to dark brown, smooth or rough surface, mostly unbranched, clearly differentiated, erect or curved. The conidia displayed a light brown to brown hue, lemon shape, fusiform, elongated ellipsoid or others with obvious spore markings and spore umbilicus. Genomic DNA was extracted from fungal colonies on infected leaves of three collections separately (Braun et al. 2003) and the internal transcribed spacer regions (ITS), actin (ACT) genes and partial translation elongation factor-l-alpha (EF) were amplified and sequenced using the primers ITS1/4 (Yin et al. 2012), ACT-512F/ACT-783R and EF 1-728F/986R (Carbone and Kohn 1999), respectively. DNA sequences of isolates were identical and deposited in GenBank (accession no. OR362754 for ITS, OR611929 for ACT and PP209106 for EF). The consensus sequences from ITS, EF and ACT showed 100%, 98.98% and 100% identical to Cladosporium strains (accession no. OQ186140.1, MT154169.1 and OL322092.1), respectively. To confirm the pathogenicity of the isolates, hydrangeas were planted in 15-cm pots containing commercial potting mix (one plant/pot). Three healthy plants were inoculated at the five to eight leaf stage by spraying 50 μL of the isolate conidial suspension (4 × 106 spores/mL) on healthy leaves. Three plants treated with sterile distilled water were used as controls. After inoculation, all plants were placed in a humidity chamber (>95% relative humidity, 26°C) for 48 h and then transferred to a greenhouse at 22/27°C. All inoculated leaves exhibited symptoms similar to those observed in the nursery 10 days after inoculation, while no symptoms were observed for control leaves. The fungus was re-isolated and confirmed to be C. tenuissimum. Based on the above morphological characterization and molecular identification, the causal agent for this leaf spot disease was identified as C. tenuissimum. Although C. tenuissimum has been reported to cause disease on H. paniculata in northern China (Li et al.2021), this is the first time that C. tenuissimum has been found on H. macrophylla in southern China. This new disease of H. macrophylla caused by C. tenuissimum is a threat to urban greening and is worth further investigation